Measuring Participation in Employer-Sponsored Health and Well-Being Programs: A Participation Index and Its Association With Health Risk Change. Issue 7 (September 2019) - Seaverson, Erin L. D.; Gingerich, Stefan B.; Mangen, David J.; Anderson, David R.
Purpose: To develop an index of participation in workplace health and well-being programs and assess its relationship with health risk status. Design: Study design comprised a retrospective longitudinal analysis of employee health risk assessment (HRA) and program participation data. Setting: Data from 6 companies that implemented health and well-being programs from 2014 to 2016. Participants: Employee participants (n = 95 318) from 6 companies who completed an HRA in 2014 to 2016. After matching those who completed the HRA in all 3 years, the longitudinal file included 38 789 respondents. Measures: Participation indicators were created for 9 different program components. The sum of these 9 components established the total participation index. Analysis: Descriptive and correlation analyses were conducted on all participation measures. Repeated-measures analysis of variance was used to assess the impact of participation level on health risk over time. Results: Higher levels of participation were associated with a greater reduction in risks, with each participation dose yielding a reduction of 0.038 risks ( P < .001). Conclusion: Results suggest that employees who participate more in workplace health and well-being programs experience more health risk improvement. The study also supports a more granular definition of participation based on the number of interactions and type of program.